2019
DOI: 10.21037/tau.2019.11.20
|View full text |Cite
|
Sign up to set email alerts
|

Testicular versus percutaneous epididymal sperm aspiration for patients with obstructive azoospermia: a systematic review and meta-analysis

Abstract: Background: Intracytoplasmic sperm injection (ICSI) is a popular treatment for male infertility due to obstructive azoospermia (OA). Testicular sperm aspiration (TESA) and percutaneous epididymal sperm aspiration (PESA) are two common sperm retrieval approaches for ICSI among men with OA. However, the comparative efficacies of TESA and PESA have been debated for more than a decade and there has been no synthesis of the available evidence. This meta-analysis compared fertility outcomes between TESA and PESA amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The spermatozoa collected by PESA are more motile than those retrieved by TESA, and laboratory processing of epididymal sperm is easier than that of testicular sperm. Furthermore, Shih et al reported that TESA and PESA yielded similar pregnancy and miscarriage rates (19). For these reasons, we believe that PESA, like TESA, is an appropriate and convenient way to obtain sperm for ICSI in cases of patients with orgasmic dysfunction and anejaculation.…”
Section: Discussionmentioning
confidence: 83%
“…The spermatozoa collected by PESA are more motile than those retrieved by TESA, and laboratory processing of epididymal sperm is easier than that of testicular sperm. Furthermore, Shih et al reported that TESA and PESA yielded similar pregnancy and miscarriage rates (19). For these reasons, we believe that PESA, like TESA, is an appropriate and convenient way to obtain sperm for ICSI in cases of patients with orgasmic dysfunction and anejaculation.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies showed different fertilization rates and miscarriage rates between TESA and PESA [14,[33][34][35]. A systematic review in 2019 gathered previous study data and found that there were no significant differences in pregnancy or miscarriage rates between the TESA and PESA treatment groups, although the fertilization rate was slightly higher using PESA and the implantation rate was numerically higher using TESA [16]. In our study, the fertilization rate, 2PN cleavage rate, implantation rate, no embryo suitable for transfer cycles rate, biochemical pregnancy rate, clinical pregnancy rate, ectopic pregnancy rate, singleton pregnancy rate, and twin pregnancy rate did not differ among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the source of sperm affects ICSI outcomes in OA patients is still debatable, and studies from different reproductive centers have not been unanimous [ 13 15 ]. A systematic review and meta-analysis in 2019 collected previous studies and found that there were no significant differences in pregnancy or miscarriage rates between TESA and PESA treatment groups, although the fertilization rate was slightly higher using PESA and the implantation rate was numerically higher using TESA [ 16 ]. In addition, there is little evidence for the superiority of TESA or PESA, which is in accordance with a previous synthesis in the Cochrane Database [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that there was no evidence of differences between the groups in the clinical outcomes and development of the children. A systematic review and meta-analysis performed in 2019 that compared fertility outcomes of TESA and PESA among men with obstructive azoospermia (OA) undergoing ICSI revealed that TESA and PESA yielded similar pregnancy and miscarriage rates for couples receiving ICSI because of OA ( 13 ). However, Ben-Ami I et al ( 14 ) revealed that compared with ejaculated sperm cycles, TESA cycles had a significantly higher implantation rate (20.7% vs. 5.7%), higher pregnancy rate (42.5% vs. 15.1%), and higher LBR (27.5% vs. 9.4%) ( 15 ).…”
Section: Discussionmentioning
confidence: 99%